The crisis of the production and circulation of academic knowledge in Educational Psychology - Álvarez de León, Alicia; Fauré, Jaime (Re-presentaciones: Periodismo, comunicación y sociedad, 2022)
The industry of production and circulation of contemporary academic knowledge is part of a social system, economic and cultural capitalist who has reconfigured traditional socio-cultural practices linked to academic research under the excuse of improving both their quantity and their quality. In this paper, we reflect on this industry and, more importantly, on the effects it appears to have on the production and circulation of academic research, especially in the field of educational psychology. Subsequently, we also reflected on the emergence of certain decolonial stances that question capitalist discourse and offer alternatives for change. To conclude, we imagine some transformation coordinates based on decolonial discourses.